Perceived Usefulness and Use of Open Educational Resources among Postgraduate Students in Federal Universities in South-West, Nigeria - Esan, Adedoyin Oluwatosin; Ifijeh, Blessing Ajelomohie; Chanomi, Peter Omamode (Communicate: Journal of Library and Information Science, 2024)
The study investigated postgraduate students at federal universities in southwest Nigeria perception and use of open educational resources (OER). To meet the research goal, one research question and one hypothesis were formulated. This study adopted descriptive survey design of the correlational type as its research design. 9,436 master's degree candidates from Federal Universities in South-West Nigeria make up the study's population. This study has a sample size of 377. The sample size determination table by Krejcie and Morgan (1970) was used to derive this. The quota sampling technique was used to collect the sample for this investigation. This was obtained by collecting 4% from each of the different faculties in the study universities. The results showed that there is a high level of perceived usefulness of open educational resources among postgraduate students in federal universities in South-West Nigeria Additionally, there is a low negative relationship between perceived usefulness and use of OER by postgraduate students in south-west federal universities in Nigeria. As a result, university administration and libraries are urged to support the use of open educational resources by planning conferences, seminars, and workshops to raise awareness of their use, OER should also be added to the use of library curriculum and this should be a compulsory course for all students in order to promote positive awareness.